Social entrepreneurship, psychological coaching as a developer of competences - Martins, Sofia (2018)
The objective of the study was to identify psychological and personality traits linked to social entrepreneurship in a sample of higher education students, and to highlight the usefulness of psychological coaching as a catalyst tool for the entrepreneurial psychological characteristics evidenced by students, in order to promote social entrepreneurship. The existence of social initiatives that aim to promote entrepreneurship is considered of high importance for society, in order to create value. Some authors conclude that social entrepreneurship arose due to the inability of governmental entities to respond to social problems, whether due to budgetary or even political issues. Social entrepreneurship arises in turbulent contexts of crisis and economic, social and environmental challenges. Despite being considered a new typology of entrepreneurship, social entrepreneurs have been present in society for a long time and can be signaled throughout history, and are motivated by promoting the welfare of society, thus having a social mission. The Portuguese Entrepreneurial Psychological Traits Inventory and the Big Five Inventory-44 were used as data collection materials on a sample of 224 higher education students. Our study identified that the students of the sample showed reasonably high scores in both entrepreneurial traits as well as in personality traits. We concluded that, not withstanding the high scores, only 6 students answered that they were thinking of developing an entrepreneurial project, making the implementation of a psychological coaching program, aiming at enhancing students’ skills and understanding of an entrepreneurial career, pertinent given the present economical situation in Portugal.